Characterization of Macrophage-Like Cells in Retinal Vein Occlusion Using En Face Optical Coherence Tomography - Zeng, Yunkao; Zhang, Xiongze; Mi, Lan; Gan, Yuhong; Su, Yongyue; Li, Miaoling; Yang, Ruijun; Zhang, Yining; Wen, Feng (Frontiers in Immunology, 2022)
Purpose To investigate the clinical features of a macrophage-like cell (MLC) obtained by en face optical coherence tomography (OCT) in retinal vein occlusion (RVO). Methods The study involved 36 patients with treatment-naïve unilateral acute RVO, including 21 branch RVO (BRVO) and 15 central RVO. Vessel density and macular thickness were quantified using OCT angiography. A 3-μm en face OCT slab on the inner limiting membrane in the optic nerve head (ONH) region or macular region was used to visualize the MLCs. The MLCs were binarized and quantified using a semiautomated method. The unaffected fellow eyes served as the control group. Results The morphology of MLCs appeared larger and plumper in RVO eyes. The mean MLC density in the ONH and macular regions was 2.46 times and 2.86 times higher than their fellow eyes, respectively (p < 0.001). The macular MLC density of the occlusive region was significantly lower than that of the unaffected region in BRVO (p = 0.01). The ONH and macular MLC densities in the non-perfused region were significantly lower than those in the perfused region in all RVO eyes (p < 0.001). The ONH MLC density in RVO eyes was negatively correlated with radial peripapillary capillary vessel density (r = −0.413, p = 0.012). Both ONH and macular MLC densities were positively correlated with macular thickness (r = 0.505, p = 0.002; r = 0.385, p = 0.02, respectively). Conclusion The increased density and changes of morphology characterized by OCT may indicate generalized activation and aggregation of MLCs in RVO. More MLCs are recruited in the perfused region rather than the non-perfused region. RVO eyes with a higher density of MLCs tend to suffer from the thicker macula.